Loss of Natural Habitats: High-Altitude Vegetation, Pantanal (Research, Society and Development, 2022)
The objective of this study is to quantify the spatiotemporal variation of high-altitude grassland (Campos de Altitude) in two different study areas between 1985 and 2020. First, the types of vegetation present in both areas were classified using a false-color (Red, Green, Blue) composition, with the channels replaced by mid-infrared, near-infrared, red, respectively. Following the definition of vegetation classes and the creation of polygons over them, they were superimposed on the NDVI product (1985 and 2020) to obtain the maximum and minimum values of the index and to identify which value ranges each class would be in. Next, a multitemporal false-color composition was carried out with the modification of the Red channel by the NDVI 1985 product, the Green channel by the NDVI 2020 product and the Blue channel without any changes. The results show that the total area of Campos de Altitude decreased between 1985 and 2020 in both study areas, with area 1 losing 31.93% and area 2 losing 35.12%, whereas the vegetation of denser strata (arboreal) increased in its spatial distribution in both study areas, with area 2 gaining the most (230%). There was a noticeable increase in arboreal vegetation in the two study areas during the years analyzed. The tendency for the fraction of arboreal vegetation cover to increase is in line with the decrease in Campos de Altitude vegetation, and this phenomenon may be related to environmental factors such as temperature variations, amount of rainfall, solar radiation, and soil composition.